A cross-sectional study: family communication, anxiety, and depression in adolescents: the mediating role of family violence and problematic internet use - Xin-cheng Huang; Yue-ning Zhang; Xiao-yu Wu; Yang Jiang; Hao Cai; Yu-qian Deng; Yuan Luo; Li-ping Zhao; Qin-ling Liu; Sheng-yue Luo; Yan-yan Wang; Li Zhao; et al. (BMC, 2023)
Abstract Objective The objective of this study is to explore the relationship between family communication, family violence, problematic internet use, anxiety, and depression and validate their potential mediating role. Methods The study population consisted of Chinese adolescents aged 12 to 18 years, and a cross-sectional survey was conducted in 2022. Structural equation models were constructed using AMOS 25.0 software to examine the factors that influence adolescent anxiety and depression and the mediating effects of problematic internet use and family violence. Results The results indicate that family communication was significantly and negatively related to family violence (β = -.494, p < 0.001), problematic internet use (β = -.056, p < .05), depression (β = -.076, p < .01), and anxiety (β = -.071, p < .05). And the finds also indicate that family violence mediated the relationships between family communication and depression (β = -.143, CI: -.198 -.080), and between family communication and anxiety (β = -.141; CI: -.198 -.074). Chain indirect effects between family communication and depression (β = -.051; CI: -.081 -.030) or anxiety (β = -.046; CI: -.080 -.043) via family violence and then through problematic internet use were also found in the present study. Conclusions In conclusion, positive family communication is crucial in reducing anxiety and depression in adolescents. Moreover, problematic internet use and family violence mediate the effects of positive family communication on anxiety and depression. Therefore, improving family communication and promoting interventions aimed at reducing family violence and problematic internet use can help reduce anxiety and depression in adolescents, thus promoting their healthy development.